Respuestas
Respuesta dada por:
1
La formula ya despejada es:
a = f /m
a = f /m
Respuesta dada por:
5
*****Respuesta:*****
![f=ma f=ma](https://tex.z-dn.net/?f=f%3Dma)
![\frac{f}{m}=a \frac{f}{m}=a](https://tex.z-dn.net/?f=+%5Cfrac%7Bf%7D%7Bm%7D%3Da+)
![a= \frac{f}{m} a= \frac{f}{m}](https://tex.z-dn.net/?f=a%3D+%5Cfrac%7Bf%7D%7Bm%7D+)
⇒El resultado del despeje es:
------>R//:
⇒El resultado del despeje es:
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años